2012
DOI: 10.2165/11599470-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

The Cost Effectiveness of Human Papillomavirus Vaccines

Abstract: Based on the currently available literature, it appears that the addition of boys to a vaccination programme generally exceeds traditional cost-effectiveness thresholds. The MSM population represents a potential additional target for routine HPV vaccination; however, more cost-effectiveness studies are required before making such a policy change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 80 publications
6
50
0
Order By: Relevance
“…42,43 Indeed, multiple early modelling studies reported that vaccinating boys is less costeffective than achieving high uptake rates in females. 44,45 However, many early economic models did not account for marginal administration costs, inadequate uptake rates in females, the burden of noncervical diseases (e.g., including oral cancer and genital warts), the MSM population, sexual exploration with same-sex partners, individuals engaging in sexual activity outside their country or "herd," or the recent recommended shift from three to two doses of the vaccine. 46,47 What new evidence could support more widespread HPV vaccination programs for boys?…”
Section: Costmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Indeed, multiple early modelling studies reported that vaccinating boys is less costeffective than achieving high uptake rates in females. 44,45 However, many early economic models did not account for marginal administration costs, inadequate uptake rates in females, the burden of noncervical diseases (e.g., including oral cancer and genital warts), the MSM population, sexual exploration with same-sex partners, individuals engaging in sexual activity outside their country or "herd," or the recent recommended shift from three to two doses of the vaccine. 46,47 What new evidence could support more widespread HPV vaccination programs for boys?…”
Section: Costmentioning
confidence: 99%
“…2,48 Many modelling studies do not consider that Canadian men will not be protected if they have sexual contact with individuals from countries without an HPV vaccine program or with an HPV vaccine program that has very low uptake rates (e.g., Japan). 49 Contradicting earlier modelling studies, 44,45 some recent economic analyses have suggested that routine HPV vaccination for boys is costeffective. 46,49 A 2015 study reported that offering the HPV vaccine to Canadian males could save $8 million to $28 million over the lifetime of the modelled cohort, 50 but, crucially, this study did not model for the indirect protection that heterosexual males would receive from HPV vaccination in females through herd immunity.…”
Section: Costmentioning
confidence: 99%
“…Pharmacoeconomic modelling proved various degrees of HPV vaccination costeffectiveness for many countries (9)(10)(11)(12) and it was used to make decisions on their reimbursement. Also, HPV testing has proven to be cost-effective in many countries (13) but such analyses for Poland have not been performed yet.…”
Section: Introductionmentioning
confidence: 99%
“…16 Studies have shown that it is cost-effective to vaccinate either all men or selectively young MSM. 7,17,18 Studies have documented national-level effect of female HPV vaccination. 19 Male HPV vaccination, in addition to the existing female HPV vaccination programs, may help achieve herd immunity.…”
Section: Introductionmentioning
confidence: 99%